The Influence of Impulse Buying and Product Quality on Purchasing Decisions at Super Indo Metro Sunter with Price Discounts as a Moderator - Suryono, Imam; Bonfilia, Levina; Diansyah, Diansyah (Dinasti Publisher, 2026)
This study investigates the influence of impulse buying and product quality on purchase decisions, with discount as a moderating variable among Superindo Metro Sunter consumers. Using a quantitative causal design, data were collected from 140 respondents through questionnaires and analyzed with Structural Equation Modelling (SEM) via SmartPLS. Findings reveal that impulse buying positively and significantly affects purchase decisions, while product quality shows no significant impact. Discounts directly enhance purchase decisions and significantly moderate the relationship between impulse buying and purchase decisions in a negative direction, suggesting that discounts shift consumer behavior from emotional impulses toward more rational, value-driven choices. However, discounts do not moderate the effect of product quality on purchase decisions. These results highlight that emotional and promotional factors, particularly impulse buying and discounts, play a stronger role than product quality in shaping consumer decisions in retail contexts. The study offers practical insights for retail managers to design effective marketing strategies, provides references for future research, and helps consumers better understand the drivers of their purchasing behavior.